Establishing historical sample data is essential for identification of unaccounted Australian soldiers from WWI, WWII, and the Korean War. Issue 5 (2nd September 2020) - Connell, Jasmine R.; Ghaiyed, Andrew P.; Chaseling, Janet; Mellick, George D.; Bernie, Andrew; Brownlie, Jeremy C.; Wright, Kirsty M.
ABSTRACT: Mitochondrial DNA (mtDNA) is used for identification of Australian military personnel whose remains are recovered from historical conflicts. A mtDNA sample database does not exist for Australian soldiers that served in World War I (WWI), World War II (WWII) and the Korean War, meaning it is unknown what common haplotypes may have existed among these soldiers, risking identification errors. Haplotype diversity (position 16, 024 to 548) was examined in a sample of 254 unrelated WWII-era European-Australians. Of these, 220 different haplotypes were observed, and it is estimated that between 18% and 29% of Australian soldiers who served in historical conflicts have common haplotypes (95% CI). This research demonstrates that mtDNA control region analysis of historical military remains will provide a lower than expected power of discrimination given the population structure of the time, and enlistment policies targeting Australians of European decent. The point estimates for 52% of the common haplotypes obtained in the historical European-Australian sample were not represented in the confidence intervals for European and Western-European EMPOP data. Creation of targeted sample data reflecting correct ancestry of the WWI and II soldiers and additional mtDNA and Y-STR analysis are essential to avoid misidentification of Australian soldiers from historical conflicts.